AB0381 Change is good, but what is better? retrospective study in clinical practice first switch with different biological therapies in rheumatoid arthritis. (15th June 2017) - Ojeda, FA; Pérez-García, C; Beltran, E; Pros, A; Salman-Monte, T; Castro, F; Polino, L; Corzo, P; Carriόn, I; Castell, S; Benito, P
Abstract : Background: The effectiveness of the switch when the first anti-TNF failure in patients with rheumatoid arthritis has been demonstrated in multiple studies. But what is more effective, if you make the switch to another anti-TNF or another molecule, is not clearly defined. Objectives: A retrospective study was performed in clinical practice to determine if there is a response to DAS 28 at 6 months of change and whether there is a difference in response if the switch is performed on another anti-TNF or another biological. Methods: From a total of 254 that met ACR 2010 criteria for RA, which have been biologically treated at Rheumatology of the Parc Salut Mar from 2000 to 2016, 61 (24%) were the first switch and the DAS 28 response at 3 and 6 months of follow-up. The following variables were analyzed: age, sex, years of evolution RA, erosions, FR, ACPA, type of biological treatment, DAS 28 at the start of the switch, 3 months and 6 months, % of patients presenting DAS 28 <2, 6 at 6 months.The statistical study was performed with SPSS 20 for paired and independent quantitative variables with Student's T and chi2 for qualitative variables Results: Of the total of 61 first treatment changes, 27 (44.3%) were to another anti-TNF alpha, 23 (37.7) to tocilizumab (TCZ), 7 to abatacept (11.5%) and 4 to RTX (6, 6). The demographic and response data DAS 28 are shown in Table 1 . There are no differences in the years of evolution, % of women, FR or ACPA positive, erosions and disease activity, as measured by DAS 28, before the switch, between The two groups (anti-TNF vs non-anti-TNF). Patients in the anti-TNF group were slightly younger than non-anti-TNF.When the DAS 28 response is evaluated at 3 and 6 months, modifying the treatment is effective (DAS 28 beginning 4, 40 vs DAS 28 6 months 2.8 p<0.001). When assessing the response to change, there is no difference in the DAS 28 response at 3 months or 6 months, if you switched to anti-TNF or non-anti-TNF (3.18 vs 2.52 p=0.122). When comparing the patients with anti TNF alpha vs TCZ, 62.5% of the patients with TCZ are in remission compared to 38, 5% (p=0.047). Conclusions: In this retrospective study in daily clinical practice, it is evident that the change in treatment after failure of the first biological one, without differences if the change is to an anti TNF or another treatment. The percentage of patients who are remission at 6 months is higher if the change is at TCZ. Given the small number of patients, larger studies would be needed to confirm the results. References: Johnston SS et col. Comparison of Biologic Disease-Modifying Antirheumatic Drug Therapy Persistence Between Biologics Among Rheumatoid Arthritis Patients Switching from Another Biologic. Rheumatol Ther. Disclosure of Interest: None declared